2020
DOI: 10.1111/medu.14268
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ preference for returning to the clinical setting during the COVID‐19 pandemic

Abstract: Objectives The coronavirus disease 2019 (COVID‐19) pandemic has led to widespread disruptions in the clinical education of medical students. In managing students’ return to the clinical setting, medical schools face the challenge of balancing education, service and risk considerations. To compound this challenge, medical students may prefer not to re‐enter during a period of great uncertainty, leading to substantive downstream sequelae on individual, institutional and national levels. Understanding students’ v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 15 publications
(15 reference statements)
6
106
2
3
Order By: Relevance
“…Editor -As fourth-year medical students in the United Kingdom who have had to adapt to working from home amidst the nationwide cancellation of clinical placements, we read with interest Compton et al's survey assessing the prevalence of medical students' preference for re-entering clinical environments during the coronavirus disease 2019 (COVID-19) pandemic. 1 The finding that approximately two-thirds of surveyed students expressed a preference to return to clinical placements resonates with us. 1 Following the cancellation of undergraduate clinical learning activities, our institution provided a series of online problem-based learning seminars to ensure we met our learning objectives.…”
Section: Response To: 'Medical Students' Preference For Returning To mentioning
confidence: 68%
“…Editor -As fourth-year medical students in the United Kingdom who have had to adapt to working from home amidst the nationwide cancellation of clinical placements, we read with interest Compton et al's survey assessing the prevalence of medical students' preference for re-entering clinical environments during the coronavirus disease 2019 (COVID-19) pandemic. 1 The finding that approximately two-thirds of surveyed students expressed a preference to return to clinical placements resonates with us. 1 Following the cancellation of undergraduate clinical learning activities, our institution provided a series of online problem-based learning seminars to ensure we met our learning objectives.…”
Section: Response To: 'Medical Students' Preference For Returning To mentioning
confidence: 68%
“…Compton et al surveyed medical students of Duke-NUS Medical School in Singapore, less than a month after the pandemic onset, and found that about a third of the surveyed 179 students would not prefer to return to the clinical setting; the students' willingness to return to the clinical environment was associated with personal characteristics and students' perceptions about the risk to the healthcare systems [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is unclear when the situation will be under control and there is a possibility of a recurrence of the epidemic due to various factors, such as intensive care capacity, development of vaccines and treatments, and the in ux of visitors from foreign countries (17,18), CC may be discontinued again. Furthermore, some medical students may not want to return to the clinical setting under the current circumstances (19). Therefore, the demand for online alternatives will be high.…”
Section: Discussionmentioning
confidence: 99%